Methods of leaf sampling in teak (tectona grandis) for nutrient analysis - K. Sudhakara (2016)
A study was conducted in 10-y-old teak plantations of Nilambur, Kerala, India, to standardise the canopy height, time of sampling, leaf rank and diameter class of trees from which to collect leaf samples for the determination of N, P and K concentrations. Seasonal variation in the foliar N, P and K concentrations was also determined for a period of thirteen months starting from August 1993 to August 1994. Since mean nutrient concentration was high and varied little among the samples, leaves obtained from the bottom position of the crown during the time interval 0900 h to 1100 h were taken as the standard. Similarly, the second leaf rank from trees belonging to the diameter class (16.75-20 cm) were found to be ideal for sampling. Foliar nutrient concentrations were higher from June to September, which received high rainfall and were low during the drier months of January to Apri